Correlation between the DNA methylation and gene expression of IGFBP5 in breast cancer - (:unkn) unknown (IOS Press, 2016)
BACKGROUND: The insulin-like growth factor binding protein5 (IGFBP5) is often dysregulated in human cancers and considered neither a tumor suppressor nor an oncogene. OBJECTIVE: We aim to examine the reason of the changeable gene regulation of IGFBP5 in the case of methylation in breast cancer. METHODS: We used methyl-specific polymerase (MSP) chain reaction to detect CpG methylation of IGFBP5 promoter and exon-I in breast cancer and adjacent tissues. Gene expression is evaluated by quantative polymerase chain reaction (qPCR). RESULTS: IGFBP5 methylation was detected in 24 of 58 (41%) and 54 of 56 (96.5%) promoter and exon-I site respectively in tumor tissues. In adjacent tissues 17 of 58 (29%) and 53 of 56 (96.5%) was methylated. IGFBP5 expression was higher estrogene receptor (ER)(+) than ER(-) patients (p = 0:0549). Beside, we found a positive correlation between the expression of IGFBP5 and G2 tumor grade (p = 0:0131). However, no correlation was observed between IGFBP5 expression and age, menopause or the presence of lymph node metastasis (p > 0:05). CONCLUSIONS: In summary, our results showed that IGFBP5 promoter and exon-I methylation did not have any differences between tumor and adjacent tissues so that IGFBP5 methylation did not change IGFBP5 gene regulation in breast cancer. This is the first study investigating the IGFBP5 gene methylation in breast cancer. © 2016 - IOS Press and the authors.
Keywords: breast cancer; IGFBP5; methylation; MSP; promoter